Personal Health of Spine Surgeons Can Impact Perceptions, Decision-Making and Healthcare Delivery During the COVID-19 Pandemic - A Worldwide Study - Arash J. Sayari; Garrett K. Harada; Philip K. Louie; Michael H. McCarthy; Michael T. Nolte; Gary M. Mallow; Zakariah Siyaji; Niccole Germscheid; Jason P.Y. Cheung; Marko H. Neva; Mohammad El-Sharkawi; Marcelo Valacco; et al. (Neurospine, 2020)
Objective To determine if personal health of spine surgeons worldwide influences perceptions, healthcare delivery, and decision-making during the coronavirus disease 2019 (COVID-19) pandemic. Methods A cross-sectional study was performed by distributing a multidimensional survey to spine surgeons worldwide. Questions addressed demographics, impacts and perceptions of COVID-19, and the presence of surgeon comorbidities, which included cancer, cardiac disease, diabetes, obesity, hypertension, respiratory illness, renal disease, and current tobacco use. Multivariate analysis was performed to identify specific comorbidities that influenced various impact measures. Results Across 7 global regions, 36.8% out of 902 respondents reported a comorbidity, of which hypertension (21.9%) and obesity (15.6%) were the most common. Multivariate analysis noted tobacco users were more likely to continue performing elective surgery during the pandemic (odds ratio [OR], 2.62; 95% confidence interval [CI], 1.46–4.72; p = 0.001) and were less likely to utilize telecommunication (OR, 0.51; 95% CI, 0.31–0.86; p = 0.011), whereas those with hypertension were less likely to warn their patients should the surgeon become infected with COVID-19 (OR, 0.57; 95% CI, 0.37–0.91; p = 0.017). Clinicians with multiple comorbidities were more likely to cite personal health as a current stressor (OR, 1.32; 95% CI, 1.07–1.63; p = 0.009) and perceived their hospital’s management unfavorably (OR, 0.74; 95% CI, 0.60–0.91; p = 0.005). Conclusion This is the first study to have mapped global variations of personal health of spine surgeons, key in the development for future wellness and patient management initiatives. This study underscored that spine surgeons worldwide are not immune to comorbidities, and their personal health influences various perceptions, healthcare delivery, and decision-making during the COVID-19 pandemic.